"Stoned": Schneiderian first-rank symptoms as a manifestation of bilateral obstructive urolithiasis - Huber, Johannes; Huber, Christian G.; Lambert, Martin; Hohenfellner, Markus (The British journal of psychiatry, 2010)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0007125000008515/resource/name/firstPage-S0007125000008515a.jpg